INFLUENCE OF TYPE 2 DIABETES ON THE FUNCTION OF THE CENTRAL NERVOUS SYSTEM - Aramovna, Djuraeva Zilola; Muxlisa, Boltayeva; Elnura, Elliyeva; Ramziddin, Choriyev (PT. Antis International Publisher, 2024)
Diabetes mellitus (DM) is a global health problem that affects all age groups, races and ethnicities[1,3,4]. Currently, about 177 million people worldwide suffer from this disease[33,34]. According to WHO forecast, the number of patients with diabetes will increase to 300 million people by 2025[2,5,6]. Non-insulin-dependent diabetes mellitus (NIDDM) is the most common and accounts for about 90% of diabetes cases[7,8,9].